Dashboard Monitoring Atmospheric Corrosion Sensor in Material Metal Using Laravel Framework - Nima Rohmalia; Gigih Forda Nama; Nining Purwasih (Journal of Engineering and Scientific Research, 2021)
Corrosion is a chemical reaction that occurs in materials made of iron such as steel.  Steel that is experiencing corrosion will appear dark brown spots, the longer it is getting more and more and can cover the entire surface. Corroded steel will result in a major deterioration and structural failure because the thickness of the steel will decrease over a period of time, so the safety of the building is clearly not guaranteed. Research on the tools used to detect the corrosion value of steel has been carried out. However, not using the internet of things technology. Therefore, a web-based corrosion monitoring or monitoring system was designed. The web will display data on voltage and temperature values ??in the form of numbers and charts. In addition, the website can also send SMS and Whatsapp message notifications if the value obtained exceeds the threshold. In developing this website using the prototype method, Laravel Framework, PHP and Java programming languages, MySQL database, Guzzle, and Whatspie as automatic message sending bots. System can provide information of monitoring regarding dummy, active and delta voltage along with their time and temperature.